Interest rate risk of life insurers: Evidence from accounting data - Axel Möhlmann (Deutsche Bundesbank, 2017)
Life insurers are exposed to interest rate risk, and their liability side is typically more sensitive to interest rate changes than their asset side. This paper develops an accounting-based measure of interest rate sensitivity. My approach uses the coexistence of historical cost and market value accounting, which permits the observation of valuations for different discount rates. Using microdata, I show that German life insurers have a significant exposure to interest rate risk. However, there is a wide dispersion across the sector. I find that insurers' size, growth and solvency are negatively correlated with interest rate risk. The heterogeneity suggests that insurers would behave differently during times of stress, which has important implications for understanding the macroprudential risks to which the sector is exposed.
Keywords: E43; G11; G22; 330; life insurance; interest rate risk; asset liability management; duration gap